Menopause knowledge and attitude among Iranian women - Taherpour, M (J Med Life, 2015)
Objective: The present study was done to assess the effects of training on knowledge and attitude level promotion of post menopause women about menopause. Methods & Material: The research communication included 100 menopausal women aged 45-60 years, who were selected in a stratified manner (according to the economic status: poor, average, and good). The tool used was an examiners-made questionnaire, which contained 3 parts: demographic characteristics, knowledge and attitude measurement. Results: Eleven percent of the studied women had a low knowledge regarding menopause and 1% was good. After training, 27% got a good knowledge and no one remained at the low level. The attitude of 59% of the studied women regarding menopause was positive and 80% got a positive attitude after training. A significant relation was found between knowledge and attitude, before and after training. Conclusion: Despite the fact that the majority of women judge menopause as a positive incident, it seems that paying attention to their training caused the bringing to their knowledge of the natural menopause and having a healthy and jolly life.